Metal–organic framework bearing new viologen ligand for ammonia and Cr2O72− sensing. Issue 12 (1st March 2022) - Zhu, Baili; Jin, Yunpeng; Chu, Jingying; Zuo, Minghui; Cui, Shuxin
Abstract : Three MOFs based on different metal salts were synthesized, and metal salts were found to play a key role in regulating the performance of MOFs. Abstract : Three anionic metal–organic frameworks (MOFs) {[Zn3 (BTEC)2 (H2 O)(4-BCBPY)]·(H2 O)} n (1–3 ) (BTEC 4− = 1, 2, 4, 5-benzenetetracarboxylic acid anion, 4-BCBPY 2+ = 1, 1′-bis(4-cyanobenzyl)-4, 4′-bipyridinium dication) were synthesized in the reaction of 1, 2, 4, 5-benzenetetracarboxylic acid with different metal salts such as ZnNO3, ZnCl2, and ZnSO4, under solvothermal conditions in the presence of 1, 1′-bis(4-cyanobenzyl)-4, 4′-bipyridinium chloride. Single crystal X-ray diffraction analysis shows that compounds 1, 2 and 3 have MOF structures based on binuclear metal building units, which are connected by two protonated BTEC 4− ligands and three zinc ions, and the viologen cation 4-BCBPY 2+ is located in the channel to achieve charge balance. Compounds 1, 2 and 3 have good photosensitivity, respond to sunlight, UV light and blue ray, and turn blue. The D–A distance and π–π stacking distance of the discolored samples (1P, 2P and 3P ) changed. In addition, the three compounds showed visible color changes to ammonia vapor, rapidly changing from white to blue. At the same time, the three compounds exhibited fluorescence quenching to ammonia vapor and Cr2 O7 2− . It is further proved that compounds 1, 2 and 3 are fluorescent sensors with a low detection limit (for Cr2 O7 2− : 10 −5 M) and high sensitivity for ammonia vapor and Cr2 O7 2− . It was found that photochromic behavior, ammonia sensing properties can be tuned by the nature of metal salts.